Application of fine nursing management for patients undergoing simultaneous bilateral lobectomy (精细化护理干预在同期双侧肺叶切除术患者中的应用) - BAI Xue (白雪); ZHAO Ying (赵莹); ZHENG Yue (郑悦); LIU Dongying (刘东颖); LI Huiyan (李惠艳) (中西医结合护理)
Objective To investigate the effect of f fine nursing management for patients undergoing simultaneous bilateral lobectomy. Methods Totally 52 patients under simultaneous bilateral lobectomy were randomly divided into the control group and observation group, with 26 cases in each group. The control group received routine nursing interventions during perioperative period. The observation group was given fine nursing management. The indwelling time of catheter, length of postoperative hospital stay, hospitalization costs and postoperative complications were recorded. Results The indwelling time of drainage tube and length of postoperative hospital stay in the observation group were shorter than those in the control group(P＜0. 05). There was a case of pneumothorax, 1 case of stage I pressure injury, 5 cases of arrhythmia, 2 cases of breathing difficulties and 2 cases of incision infection in the observation group. There was a case of pneumothorax, 3 cases of stage I pressure injury, 5 cases of arrhythmia, 1 case of breathing difficulties, 5 cases of incision infection and 1 case of death in the control group. Conclusion Implementation of fine nursing management is effective to shorten indwelling time of drainage tube and length of postoperative hospital stay of patients undergoing simultaneous bilateral lobectomy. (目的 探讨同期双侧肺叶切除围手术期实施精细化护理干预的效果。方法 选取2015年1月—2021年12月医院收治的行同期双侧肺叶切除患者52例, 随机分为对照组和观察组, 各26例。对照组围手术期采取常规护理, 观察组围术期采取精细化护理干预。记录和分析两组患者引流管留置时间、术后平均住院日、住院费用和术后并发症。结果 观察组患者引流管留置时间、术后平均住院日较对照组缩短, 差异有统计学意义(P＜0. 05)。观察组术后发生气胸1例, I期压疮1例, 心律失常5例, 呼吸困难2例, 切口感染2例; 对照组术后气胸1例, I期压疮3例, 心律失常5例, 呼吸困难1例, 切口感染5例, 死亡1例。结论 同期双侧肺叶切除围手术期实施精细化护理干预, 能缩短患者引流管留置时间和术后平均住院日, 对促进患者术后康复具有积极意义。)